Web Peta Informasi Kodisi Jalan Kabupaten di Kecamatan Talang Kelapa Kabupaten Banyuasin - Efrilia Rahmadona; Ibrahim Ibrahim; Norca Praditya (Jurnal Talenta Sipil, 2023)
Road conditions affect the level of service and community comfort in supporting the economic, social, and cultural activities of the community, if road conditions do not support this it will hinder these activities. However, the problem in the field is the condition of the damaged roads and the reporting system that has not been integrated so repairs are slow. Therefore we need a systematic and integrated road condition reporting system so that the order of priority for handling road conditions is correct. Mapping the road network using a Web-based Geographic Information System is one of the solutions that can be used to overcome this problem. The method used in this study is the GIS application for mapping road conditions in the Talang Kelapa sub-district, Banyuasin district with a total of 143 Km of roads. After that, the mapping of the GIS application made a website so that users can access road conditions from anywhere with an internet network. The results of research on previous road conditions using the Surface Distress Index (SDI) method show that there are 4 categories of road conditions in the Talang Kelapa sub-district, namely: Heavily Damaged, Lightly Damaged, Moderate and Good. integrated with the Website, where the Website address https://peta_jalan_banyuasin.gis.co.id/ can be accessed.